Monitoring sugar content in soft drinks - Portuguese initiatives towards public health. - Lopes, Andreia (2021)
Objectives: To evaluate sugar content in soft drinks available on the Portuguese market against the sugar target values recommended by EIPAS; to know current reality and support policy makers.